Factor Affected to Success of One Day Surgery in Open Appendectomy: Yasothron Hospital Experienced - Cheepcharoenrat, Niyom; Nethan, Chompunut (Journal of The Department of Medical Services, 2022)
Background: Open appendectomy was an emergency operation. ERAS (enhanced recovery after surgery) could decrease the length of stay (LOS) to less than 24 hours and decrease medical costs. If we studied the factor that affected the patients with open appendectomy discharge within 24 hours, we would have clinical practice guideline to decrease LOS. Objective: Studied factor affecting the success of patient with open appendectomy who had LOS less than 24 hours. Methods: A case-control study was conduct in the In Patient Department and collected data form medical record of Yasothon hospital between 1 October 2020 and 30 September 2021. Study factor affected success LOS less than 24 hours and analyzed by multiple logistic regression. Results: The factor affected to success were age <15 years (OR 4.31; 95%CI: 1.08, 17.17), 15-30 years (OR 6.08; 95%CI: 1.68, 21.92), 30-45 years (OR 11.40; 95%CI: 3.02, 43.05), suppurative appendicitis (OR 9.29; 95%CI: 1.89, 45.75), oral NSAID (OR 2.96; 95%CI: 1.50, 5.84), admission time at 08:01-16:00 o’clock (OR 31.57; 95%CI: 4.06, 245.44), duration of symptom onset no more than 24 hours (OR 6.73; 95%CI: 1.37, 32.95), waiting time for surgery no more than 4 hours. (OR 1.95; 95%CI: 1.05, 3.64) Conclusion: The patients with open appendectomy who were less than 45 years old, suppurative appendicitis, oral NSIAD, admission time at 08:01-16:00 o’clock, duration of symptom onset no more than 24 hours and waiting time for surgery no more than 4 hours would have the length of stay (LOS) less than 24 hours.